The Olympic Games of 1994 and Norwegian image - Lapkūnaitė, Žydronė (Information & Media, 1994)
The article is representing the main ideas, that served as a background of the project "Norwegian Image in Lithuania". It was expected that the Olympic Games period would be very fruitful in constructing and developing the image of the Olympic Games host country - Norway. The course of the preparations for the survey of Norwegian image in Lithuania is presented and the main topics are outlined in this paper.
Keywords: -